Bond Graphs for Modelling, Control and Fault Diagnosis of Engineering Systems - Borutzky, Wolfgang; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book presents theory and latest application work in Bond Graph methodology with a focus on: • Hybrid dynamical system models, • Model-based fault diagnosis, model-based fault tolerant control, fault prognosis • and also addresses • Open thermodynamic systems with compressible fluid flow, • Distributed parameter models of mechanical subsystems. In addition, the book covers various applications of current interest ranging from motorised wheelchairs, in-vivo surgery robots, walking machines to wind-turbines.The up-to-date presentation has been made possible by experts who are active members of the worldwide bond graph modelling community. This book is the completely revised 2nd edition of the 2011 Springer compilation text titled Bond Graph Modelling of Engineering Systems -Theory, Applications and Software Support. It extends the presentation of theory and applications of graph methodology by new developments and latest research results. Like the first edition, this book addresses readers in academia as well as practitioners in industry and invites experts in related fields to consider the potential and the state-of-the-art of bond graph modelling.
Introduction -- Part I: Bond Graph Theory and Methodology -- Bond Graph Modelling and Analysis of Hybrid Systems -- Controlled Switched Junctions. -Causally Dynamic Hybrid Bond Graphs -- Part II: Bond Graph Modelling for Control, Fault Diagnosis, and Fault Tolerant Control -- Fault Diagnosis and Fault Tolerant Control of Hybrid Systems Using Bond Graphs -- Bond Graph-based Fault Diagnosis and Prognosis of Uncertain Systems -- Bond Graphs for Supervision of Industrial Processes -- Part III: Thermodynamic Systems and Distributed Parameter Systems -- Bond Graph Modelling and Simulation of Thermodynamic Systems -- Fluid-flow Systems -- Bond Graph Approximation of Distributed Parameter Systems -- Part IV: Applications -- Absorbing Vibrations in a Helicopter -- Bond Graph Modelling and Control of Miniature Robots for In-vivo Surgery. -Modelling and Control of Mobile Legged Robots -- Exploitation of Renewable Energy, Bond Graph Modelling of Wind Turbines -- Bond Graph Modelling in Biomedical Engineering,Bond Graph Modelling of Biochemical Processes -- Conclusion.
Keywords: Telecommunication; Control engineering; Mechanics, Applied; Electronic circuits; Engineering mathematics; Engineering -- Data processing; Communications Engineering, Networks; Control and Systems Theory; Engineering Mechanics; Electronic Circuits and Systems; Mathematical and Computational Engineering Applications